Do Small Medium Enterprises (SMEs) Need To Adopt E-wallet? A Study Post- Covid-19 Pandemic - Apriani, Ari; Endah Retno Wuryandari, Nur (KnE Social Sciences, 2023)
SMEs are not deemed to be moving forward until they quickly implement e-payment systems into their operations. In today’s world, both online and in-person purchases are made via electronics. Many stores and malls currently provide digital payment options like QRIS (Quick Response Indonesia Standard), but few SMEs are willing to adopt it. Therefore, this research is important because during the Covid-19 pandemic, online shopping activities at e-commerce merchants for SMEs in Indonesia increased. Because SMEs must be able to adjust to situations, both during and after the pandemic by using E-Wallet as a form of payment, the results of this study can be taken into consideration by SMEs players to adopt e-wallet and make the move to digital. Based on earlier research used to develop the study’s research hypotheses, quantitative descriptive research was carried out. The Smart PLS program will be used to handle the data for 250 respondent populations dispersed across 5 regions of Indonesia. Based on the study’s findings, SMEs players may want to consider going digital and expanding their payment choices with secure, user-friendly e-wallets so that customers feel comfortable making payments. Keywords: e-wallet, intention to adopt, perceived ease of use, perceived risk, promotion